DEVELOPING THE NONFORMAL EDUCATION OF LEARNING IN MUHAMMADIYAH UNIVERSITY OF ENREKANG - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
This research is motivated by three things: (1) The learning process in schools that prioritizes the cognitive aspects that lead to convergent patterns and thought processes, while the creative thought processes, affective and psychomotor aspects receive less attention. (2) Increasing technological progress and increasing population and decreasing supply of natural resources are very demanding of the ability to adapt creatively and expertise to find creative solutions. (3) There are very few creative Indonesians found, so many unemployed people are very dependent on the available employment. They are not able to create their own jobs. There are three classic problems faced by the world of education in Indonesia in the development of creativity that have not been resolved to date, namely: (1) Lack of clear vision, mission, and goals of implementing creativity education, (2) The preparation of the curriculum is not in accordance with the expectations and needs of students such as the preparation materials, learning methods, learning media, and evaluation systems, (3) Teaching staff and facilities are inadequate, both in terms of quality and quantity. To overcome the three problems above the quality of the learning process needs to be improved, both the quality of the program and the quality of its implementation. In an effort to improve this, the managers of educational institutions need to look for strategic steps that include the preparation of learning programs and efforts to increase the competence of lecturers in an effort to develop student creativity. Likewise lecturers need to design components of the learning process that can develop student creativity which includes the design of the learning environment, student activities, learning methods and media, and evaluation techniques of learning outcomes. The program that has been prepared must be implemented in accordance with the design. Then it is evaluated to determine the level of success, obstacles encountered and the steps to solve them. This qualitative research aims to examine and analyze the effectiveness of the implementation of the learning process in the development of creativity in Non-formal Education Study Program at the University of Muhammadiyah Enrekang. This study uses a case study approach, considering the object under study consists of one unit or one unit that is seen as a case. Data were collected by observation, interview and documentation study techniques. The population of this study was 9 lecturers and 72 non-formal education students, while the sample of this study was 5 lecturers and 42 fourth grade A students determined by purposive sampling with the consideration that class B had not been effective in the lecture process. The results of this study concluded that the implementation of class A class IV semester of Non-formal Education Study Program tends to experience positive development and has obtained good results in the effort to develop student creativity. The indicators are shown in: (1) increasing PNF students working, (2) increasing passing grade grades and lowest UAS assessed as odd semester, (3) increasing the average UAS value obtained by grade A students, (4) increasing growth and the development of educational facilities, (5) increasing the achievement of championship achievements in the extracurricular field. From the perspective of empowerment the results of this study have implications for the development of a broad learning process that is the emergence of a shared awareness among education managers and lecturers that the lecture process is not only for transferring knowledge, but also developing all the potential of students, including the creative potential of students. Specific implications for the development of student creativity are the emergence of awareness of education managers and lecturers to evaluate and reorganize their programs and performance in order to improve the quality of the learning process.